PIECEWISE LINEAR APPROXIMATION OF THE SINUSOIDAL MOTION OF THE VIBROCALIBRATION COMPLEX CARRIAGE - Криворучко, Игорь (SWorldJournal, 2022)
To simplify the control of the stepper motor in the case of sinusoidal motion of the carriage of the vibro-calibration complex, it is proposed to represent this motion by the sum of segments with a fixed speed. An algorithm for calculating breakpoints and